New insights into the mechanisms of diabetic complications: role of lipids and lipid metabolism - Eid, Stephanie; Sas, Kelli M.; Abcouwer, Steven F.; Feldman, Eva L.; Gardner, Thomas W.; Pennathur, Subramaniam; Fort, Patrice E. (Diabetologia, 2019)
Diabetes adversely affects multiple organs, including the kidney, eye and nerve, leading to diabetic kidney disease, diabetic retinopathy and diabetic neuropathy, respectively. In both type 1 and type 2 diabetes, tissue damage is organ specific and is secondary to a combination of multiple metabolic insults. Hyperglycaemia, dyslipidaemia and hypertension combine with the duration and type of diabetes to define the distinct pathophysiology underlying diabetic kidney disease, diabetic retinopathy and diabetic neuropathy. Only recently have the commonalities and differences in the metabolic basis of these tissue-specific complications, particularly those involving local and systemic lipids, been systematically examined. This review focuses on recent progress made using preclinical models and human-based approaches towards understanding how bioenergetics and metabolomic profiles contribute to diabetic kidney disease, diabetic retinopathy and diabetic neuropathy. This new understanding of the biology of complication-prone tissues highlights the need for organ-specific interventions in the treatment of diabetic complications.